Use of municipal solid waste incinerator (MSWI) bottom ash in high calcium fly ash geopolymer matrix. (1st April 2017) - Wongsa, Ampol; Boonserm, Kornkanok; Waisurasingha, Chattichai; Sata, Vanchai; Chindaprasirt, Prinya
Abstract: In order to reduce municipal solid waste incinerator (MSWI) ash, the effect of replacement level of high calcium fly ash by MSWI bottom ash on fly ash based geopolymer properties were studied. The results were compared to cement matrix containing MSWI bottom ash. It showed that the 20% MSWI bottom ash replacement level produced the highest compressive strength at 7 d of 52.8 MPa. The MSWI bottom ash could replace fly ash at high dosage level of 40% and the compressive strength was still higher than that of the control geopolymer mortar. The porosity, pore size distribution, and SEM indicated that the use of MSWI bottom ash could increase the denseness and homogeneity of geopolymer and cement matrix. In addition, the increase of MSWI bottom ash level significantly increased the crystalline phases of calcite and quartz as shown in the XRD pattern and C-O stretching in the FTIR images of both matrices. Highlights: Municipal solid waste incinerator bottom ash (WA) and fly ash geopolymer was investigated. Compressive strength and microstructure of geopolymer matrix were tested. The results were compared to cement matrix containing WA. WA could increase the denseness and homogeneity of geopolymer and cement matrix.